The revolving door: State connections and inequality of influence in the US banking sector - Elise S. Brezis; Joël Cariolle (Bar-Ilan University, Department of Economics, 2017)
This paper addresses the effects of the revolving door phenomenon on the inequality of influence among firms. It shows that firms are not equal in their capacities to benefit from state connections. We first develop a theoretical model introducing the notion of "bureaucratic capital" and showing how the revolving door generates inequality in bureaucratic capital and in profits leading to inequality of influence. Then, this prediction is tested on a new database tracking the revolving door process involving the 20 biggest US commercial banks. We show that regulators who have created a large stock of "bureaucratic capital" are more likely to be hired by the top five banks after leaving public office. We then develop indices of the inequality of influence between banks. We show that banks in the top revenue quintile concentrate around 80% of the stock of revolvers. Goldman Sachs appears as the prime beneficiary of this process, by concentrating almost 30% of the revolving door phenomenon.
Keywords: D73; G01; G18; L51; 330; regulators; revolving door; rent-seeking; state connections; bureaucratic capital; inequality of influence; connected firms; corruption; unethical behavior